A supersymmetric reduction on the three-sphere - Nihat Sadik Deger; Henning Samtleben; Özgür Sarıoğlu; Dieter Van den Bleeken (Nuclear Physics B, 2015)
We present the embedding of three-dimensional SO(4)⋉R6 gauged N=4 supergravity with quaternionic target space SO(4,4)/(SO(4)×SO(4)) into D=6, N=(1,0) supergravity coupled to a single chiral tensor multiplet through a consistent reduction on AdS3×S3.